A significant portion of college students are not aware of HPV disease and HPV vaccine recommendations. Issue 7 (3rd August 2019) - Kellogg, Caitlyn; Shu, Janella; Arroyo, Ayana; Dinh, Ngoc Tuyen; Wade, Nia; Sanchez, Elizabeth; Equils, Ozlem
ABSTRACT: There is limited data on the HPV immunization status of Latino/Hispanic youth in the USA. In Los Angeles County in 2015, 54, 973 (34.3%) college students were of Latino/Hispanic background. We examined Los Angeles County college students' awareness of HPV and HPV-related disease, HPV vaccine recommendations, and their vaccination status. This study surveyed 212 Los Angeles college students from January to April 2018. In a convenience sampling study, a 31-question, IRB-approved survey was administered face-to-face to college students 18 years and older at California State University settings in Los Angeles County. Almost two-thirds of the male (65%) and half of the female (51.6%) respondents did not know that the HPV vaccine is recommended through 26 years of age, and 47.6% did not know they can get the HPV vaccine at the college student health center or youth-friendly clinics. Ethnicity, family income, and the highest level of education in the family had a significant impact on immunization rates. Self-reported and actual HPV knowledge levels were significantly associated with vaccination status. Educational strategies focusing on the logistics of receiving the HPV vaccine and HPV vaccine catch-up eligibility for college students may be effective in decreasing racial disparities in vaccine receipt.